(untitled) (Research, Society and Development, 2020)
The Planned Home Birth (PHB) refers to the modality of birth assistance that occurs in the pregnant’s house and assisted by qualified professionals. It’s considered recent in Brazil, involved by myths and challenges, resulting in few studies related with this theme. Objective: Reflect “where we are and where we go about PHB in Brazil?”. Methodology: was used the theoretical trial as a method to structure and elaborate the proposed reflection. Results: by the questions done, published studies data and current legislation, it was possible to have a PHB overview in Brazil, from the births characterization, user profiles, costs, security and legislation, to advances, challenges and perspectives. Considerations: we highlight the need and importance of giving visibility to this theme, the PHB assistance in our country need advance in many aspects. The reflective path in this theoretical trial leaves many questions and provocations to the health professionals involved direct or indirect in the birth and delivery assistance.